Izbrisna tožba - analiza aktualne sodne prakse s komentarjem - Hudej, Jasna (Podjetje in delo, 2014)
In the article the author analyses recent case law of the Supreme Court of the Republic of Slovenia regarding a claim for removal from the land register. After presenting legal issues that arose in each case and decisions reached by the court, the author critically analyses the adopted solutions and reasoning of the court.
Keywords: sodišča; sodna praksa; tožbe